Clinical conundrum: managing iron overload after renal transplantation. Issue 2 (5th February 2021) - Upadhyay, Binayak; Green, Steven D; Khanal, Nabin; Antony, Aśok C
Abstract : Iatrogenic iron overload, which is not uncommon in patients undergoing long-term haemodialysis, arises from a combination of multiple red cell transfusions and parenteral iron infusions that are administered to maintain a haemoglobin concentration of approximately 10 g/dL. Although iron overload due to genetic haemochromatosis is conventionally managed by phlebotomy, patients with haemoglobinopathies and chronic transfusion-induced iron overload are treated with iron-chelation therapy. However, the management of iron overload in our patient who presented with hepatic dysfunction and immunosuppressive drug-induced mild anaemia in the post-renal transplant setting posed unique challenges. We report on the decision-making process used in such a case that led to a successful clinical resolution of hepatic iron overload through the combined use of phlebotomy and erythropoiesis stimulating agents, while avoiding use of iron-chelating agents that could potentially compromise both hepatic and renal function.